2008
DOI: 10.1111/j.1083-6101.2008.00404.x
|View full text |Cite
|
Sign up to set email alerts
|

Limits of the Appeal to Internet in Accessing Information and Training in the Exercise of Parenting Skills in Quebec

Abstract: In this article, we define the concept of digital gap as a multidimensional construct, and account for the contradictory relations stated in the scientific literature concerning the appeal to Internet by the more or less privileged strata of society. We explore the state of the digital gap and analyze diverse policies implemented by federal and provincial governments to support accessibility to digital resources in Quebec. After presenting results of a survey with parents concerning access to information and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…On the other hand, the overwhelming majority of persons have cell phones in all income levels (Smith, 2013). So although the present review found evidence that low-SES parents may be generally less interested in using the internet for parenting information (Larose et al, 2008; Lerner et al, 2012; Mackert et al, 2009) the use of smartphone applications or texts may be a way to reach younger parents and those of all income levels. Socioeconomic differences in both access and acceptability of technology-based intervention delivery require further study.…”
Section: Concerns and Possible Limitations Of Technology-assisted Intmentioning
confidence: 66%
See 4 more Smart Citations
“…On the other hand, the overwhelming majority of persons have cell phones in all income levels (Smith, 2013). So although the present review found evidence that low-SES parents may be generally less interested in using the internet for parenting information (Larose et al, 2008; Lerner et al, 2012; Mackert et al, 2009) the use of smartphone applications or texts may be a way to reach younger parents and those of all income levels. Socioeconomic differences in both access and acceptability of technology-based intervention delivery require further study.…”
Section: Concerns and Possible Limitations Of Technology-assisted Intmentioning
confidence: 66%
“…Two additional studies identified some socio-economic differences in the acceptability of the internet as a source of parenting information. Larose, Bedard, Hammami, and Terrisse (2008) surveyed 1,406 parents of preschool children about their preferred medium of receipt for parenting information. Parents who had lower income reported that they preferred pamphlets, books, television, or radio whereas higher income parents preferred email.…”
Section: Exploring the Feasibility And Acceptability Of Technology-asmentioning
confidence: 99%
See 3 more Smart Citations